Efficacy of a Standardized Turmeric Extract Comprised of 70% Bisdemothoxy-Curcumin (REVERC3) Against LPS-Induced Inflammation in RAW264.7 Cells and Carrageenan-Induced Paw Edema - Gouthamchandra K; Sudeep HV; Chandrappa S; Raj A; Naveen P; Shyamaprasad K (Dove Medical Press, 2021)
Kuluvar Gouthamchandra,1 Heggar Venkataramana Sudeep,1 Siddappa Chandrappa,2 Amrith Raj,1 Puttaswamy Naveen,3 Kodimule Shyamaprasad1 1Department of Biomedicinal Research, R&D Centre for Excellence, Vidya Herbs Pvt. Ltd, Bangalore, Karnataka, 560105, India; 2Department of Phytochemistry, R&D Centre for Excellence, Vidya Herbs Pvt. Ltd, Bangalore, Karnataka, 560105, India; 3Department of Analytical Development Research, R&D Centre for Excellence, Vidya Herbs Pvt. Ltd, Bangalore, Karnataka, 560105, IndiaCorrespondence: Kuluvar GouthamchandraDepartment of Biomedicinal Research, R&D Centre for Excellence, Vidya Herbs Pvt. Ltd, #14A, Jigani I Phase, Bangalore, Karnataka, 560105, IndiaTel +91 80 42094158Email goutham06@gmail.comObjective: It is well known that regular turmeric extract with 95% curcuminoid is comprised of curcumin (70.07%), desmethoxycurcumin (20.28%), and bisdemethoxycurcumin (BDMC) (3.63%). In the current study for the first time, we have enriched about 3% of bisdemethoxycurcumin (BDMC) to 70% as well as named it as REVERC3 and compared anti-inflammatory activity with regular turmeric extract using in vitro and in vivo models of inflammation.Methods: To reveal the potential anti-inflammatory mechanism of action, we investigated nitric oxide (NO) scavenging, xanthine oxidase, and lipoxygenase inhibitory activity, further determined the level of pro-inflammatory cytokines, such as interleukin 6 (IL-6), tumor necrosis factor (TNF-α) and major inflammatory mediators like cyclooxygenase (COX-2) and inducible nitric oxide synthase (iNOS), inhibition in lipopolysaccharide (LPS) induced inflammation in RAW macrophage cells. In the other hand, a carrageenan-stimulated inflammatory rat model was carried out.Results: Our study findings exhibited a significant anti-inflammatory activity of REVERC3 together with nitric oxide (NO), xanthine oxidase, and lipoxygenase inhibition. Further, we attenuated the levels of cyclooxygenase (COX-2), inducible nitric oxide synthase (iNOS), interleukin (IL-6) and tumor necrosis factor (TNF-α) expressions in the LPS-elicited RAW macrophage cells. REVERC3 showed a potential anti-inflammatory activity by inhibiting carrageenan induced paw edema after 4 hr at the dose of 100mg/kg body weight.Conclusion: Thus, our findings collectively indicated that the REVERC3 could efficiently inhibit inflammation compared to regular turmeric extract. Since bisdemethoxycurcumin is a stable molecule it could be effectively used in the applications of health care and the nutraceutical industry, indeed which deserves further investigations.Keywords: lipopolysaccharide, nitric oxide, xanthine oxidase, TNF-α, IL-6, iNOS, COX2